(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Timur was born around 1336 in Transoxania near Kesh – later known as Shahrisabz – in the Kashka Darya region of what is today the Republic of Uzbekistan. He was a Turk of the Barlas tribe; this tribe, like many others, boasted a Mongol name and ancestry, but for all practical purposes it was Turkic.